Exploring the Prevalence of Alexithymia Among Medical Students and Its Impact on Their Academic Performance: A Cross-Sectional Study in Peshawar, Pakistan - Khan, Laiba Ali; Noor, Bushra; Gul, Nida; Khan, Aamir; Ullah, Saif; Hafza, Bibi; Khan, Imran; Khan, Usama; Haq, Ijaz Ul; Shahzad, Farhan; Ullah, Farid (Biological and Clinical Sciences Research Journal, 2025)
Transitioning from high school to medical college presents various psychological challenges for students, including alexithymia, a condition characterized by difficulties in identifying and expressing emotions. This study investigates the prevalence of alexithymia among medical students in Peshawar, Pakistan, and explores its potential impact on academic performance. Objective: To determine the prevalence of alexithymia among medical students, compare alexithymia levels across different academic years, and assess its association with academic performance. Methods: A descriptive cross-sectional study was conducted at Khyber Medical College, Peshawar, from September 2023 to September 2024, involving 227 medical students. Alexithymia was assessed using the Toronto Alexithymia Scale (TAS-20). Academic performance was measured based on annual marks and attendance. Data were analyzed using descriptive statistics, t-tests, and chi-square tests. Results: The study found that 122 (52.4%) students exhibited alexithymia, with a higher prevalence among female students (57.3%, n = 70 out of 122). Despite the notable prevalence of alexithymic traits, no significant association was observed between alexithymia and academic performance (p = 0.47). Most participants reported that emotional difficulties did not affect their studies, and very few sought psychiatric consultation or took leave due to emotional disturbances. Conclusion: Alexithymia is prevalent among medical students in Peshawar, particularly among females. However, the lack of a significant impact on academic performance suggests a level of resilience in students. Further research into coping strategies and support systems is recommended. Addressing alexithymia within medical education may improve both emotional well-being and academic outcomes.